Organic Products: Marketing Practices and Problems in the Plains and Hilly Regions of Uttarakhand - Singh, Surabhi (Indian Journal of Marketing, 2013)
In the present study, the investigator explored the problems perceived in marketing of organic products by farmers in Uttarakhand state of India. Descriptive research design with survey method, wherein data were collected through face-to-face structured interviews with 72 farmers in the plains and hilly regions of Uttarakhand was adopted for the present investigation. Data were analyzed with descriptive statistics and Chi square test to provide additional information about the effect of the selected variables on perceived problems. The objectives focused on the prevalent marketing practices adopted by the farmers for organic crops and to ascertain marketing related problems perceived by them with reference to organic crops. The most prominent problem in marketing of organic crops reported by the respondents in the plain areas of the state of Uttarakhand was related to ’High Production Cost’ that led to low profit, or no profit; while the largest proportion of the respondents from the hills reported ’Unavailability of an earmarked market place/shop for organic crops’ to be their biggest cause for concern. The paper further deals with the market place for transaction, distribution channels, satisfaction of the sample of farmers, information on organic crops grown, perceived problems of farmers and implications of the study.